Microstructure-sensitive fatigue crack nucleation in a polycrystalline Ni superalloy. (September 2016) - Wan, V.V.C.; Jiang, J.; MacLachlan, D.W.; Dunne, F.P.E.
Highlights: Stored energy density criterion for Ni alloy RS5 fatigue crack nucleation. Morphology, texture characterised using EBSD to construct 3D FE crystal plasticity models. Critical stored energy density 13, 300 J/m 2 (Ni-RS5) predicts cycles to crack nucleation. Local microstructural variations demonstrated influence to grain-level stress–strain response. Abstract: Large-grained polycrystalline Ni alloy RS5 has been tested in fatigue. Morphology and texture have been characterised using EBSD and utilised to construct representative 3D finite element crystal plasticity models. A stored energy criterion has been used to predict scatter in fatigue crack nucleation life and the results compared with experimental findings. Good quantitative prediction of experimental fatigue lives is obtained. The observed progressive increase in scatter with decreasing strain range is captured. The stored energies for fatigue crack nucleation determined for Ni alloy RS5 and ferritic steel and were found to be 13, 300 J/m 2 and 580 J/m 2 respectively, showing very good consistency with the corresponding Griffith fracture energies of 48, 700 J/m 2 for Ni alloy and 1900 J/m 2 for ferritic steel. Local microstructural variations are shown to influence corresponding grain-level stress–strain response. At the microstructural level, purely elastic, reversed plastic and ratcheting behaviour are all observed. In addition, plastic and elastic shakedown are also found to occur which depend upon features of the microstructure and the nature of the applied loading. These phenomena all influence fatigue crack nucleation.